The role of ketogenic diets in the therapeutic management of adult and paediatric gliomas: a systematic review - Kirsty J Martin-McGill; Nisaharan Srikandarajah; Anthony G Marson; Catrin Tudur Smith; Michael D Jenkinson (CNS Oncology)
Aim: We performed a systematic review of the evidence for effectiveness and acceptability of different ketogenic diets (KDs) in the therapeutic management of gliomas. Methods: The search strategy included searches of seven electronic databases. Data extraction and quality assessment were undertaken independently by two authors. Results: No randomized clinical trials were identified. Six studies (n = 39) met the eligibility criteria for this review – all were case series or reports and therefore at high risk of bias. All studies reported overall or progression-free survival; however the effectiveness of KD interventions could not be established. Dietary acceptability was not reported. Conclusion: The effectiveness and acceptability of KDs in the management of gliomas is unknown and high quality randomized controlled trials are needed.